Blurring the lines of race and freedom : Mulattoes and mixed bloods in English colonial America - Wilkinson, A. B. (Aaron B.) (John Hope Franklin series in African American history and culture., 2020)
"Using archival records from the colonies where intermixture was most common in North America, and records from English colonies in the Caribbean, Wilkinson is able to follow the stories of those identified as 'mixed blood, ' highlighting those people caught between monoracial categories. Wilkinson shows how the position of 'mixed people' complicated colonial systems of servitude and slavery, and that the struggle for freedom by people of blended ancestry and their families prevented colonial elites from firmly establishing a concrete socioracial order. He argues that there is a better framework than the one-drop rule for understanding early mixed-race ideologies in the English colonies. He uses the term hypodescent, indicating how a person of mixed ethnoracial ancestry is often associated with their socially inferior lineage, yet their legal or socioracial status may be elevated based on their proximity to European heritage or racial whiteness. This book combines intellectual, social, and cultural history to show how the complicated socioracial order in the colonies never fit neatly with a legal status of either bound or free"--